Faktor-Faktor yang Mempengaruhi Konversi Lahan Pertanian di Subak Sebuah, Kelurahan Kerobokan, Kecamatan Kuta Utara, Kabupaten Badung, Bali - WIRYANTINI, NI LUH RISKA; WIDYANTARA, I WAYAN; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.3, Juli 2018DO - 10.24843/JAA.2018.v07.i03.p01, 2018)
Factors Affecting Agricultural Land Conversion in the Irrigation Organization of Subak Sebuah, Kerobokan Urban Village, Sub-District of Kuta Utara, Badung Regency, Bali The research aimed to investigate the factors that affect the conversion of agricultural land and the dominant factors that affect the conversion of agricultural land in the traditional irrigation organization of Subak Sebuah, located at Kerobokan Urban Village, Sub-District of Kuta Utara, Badung Regency, Bali. The location was chosen purposively in Subak Sebuah, Kerobokan Urban Village, Sub-District of Kuta Utara, Badung Regency, Bali. The number of respondents was 70 people by using quota sampling method. This research used factor analysis. The findings showed that factors affecting the conversion of agricultural land in the Subak Sebuah are economic factors (land selling price, land leasing price, farm income, household expenditure), social factors (following neighbors, age, and the number of family members working outside the agricultural sector) and land conditions factors (availability of irrigation water, access to irrigation water, land area before conversion, and location of land). The dominant factors affecting the conversion of agricultural land in Subak Sebuah, Kerobokan Urban Village, Sub-District of Kuta Utara, Badung Regency, Bali are the economic factors.